Incestuous sisters: mate preference for brothers over unrelated males in Drosophila melanogaster. - Adeline Loyau (Public Library of Science (PLoS), 2012)
The literature is full of examples of inbreeding avoidance, while recent mathematical models predict that inbreeding tolerance or even inbreeding preference should be expected under several realistic conditions like e.g. polygyny. We investigated male and female mate preferences with respect to relatedness in the fruit fly D. melanogaster. Experiments offered the choice between a first order relative (full-sibling or parent) and an unrelated individual with the same age and mating history. We found that females significantly preferred mating with their brothers, thus supporting inbreeding preference. Moreover, females did not avoid mating with their fathers, and males did not avoid mating with their sisters, thus supporting inbreeding tolerance. Our experiments therefore add empirical evidence for inbreeding preference, which strengthens the prediction that inbreeding tolerance and preference can evolve under specific circumstances through the positive effects on inclusive fitness.